2010
DOI: 10.1038/ng.663
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study identifies a susceptibility locus for refractive errors and myopia at 15q14

Abstract: Refractive errors are the most common ocular disorders worldwide and may lead to blindness. Although this trait is highly heritable, identification of susceptibility genes has been challenging. We conducted a genome-wide association study for refractive error in 5,328 individuals from a Dutch population-based study with replication in four independent cohorts (combined 10,280 individuals in the replication stage). We identified a significant association at chromosome 15q14 (rs634990, P = 2.21 × 10−14). The odd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
154
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(171 citation statements)
references
References 37 publications
11
154
4
1
Order By: Relevance
“…Twin studies add further support, indicating heritability values between 0.5 and 0.90 (9)(10)(11). Genome-wide association studies have identified putative gene loci on chromosomes 13q (12) and 15q (13,14), as well as genetic variants in CTNND2, as being associated with myopia (15). Recently, a missense variant in LEPREL1 (encoding prolyl 3-hydroxylase 2 [P3H2]), a 2-oxoglutarate-dependent dioxygenase that hydroxylates collagen molecules, was associated with an autosomal-recessive form of high myopia and early-onset cataracts in an Israeli-Bedouin kindred (16).…”
Section: Introductionmentioning
confidence: 82%
“…Twin studies add further support, indicating heritability values between 0.5 and 0.90 (9)(10)(11). Genome-wide association studies have identified putative gene loci on chromosomes 13q (12) and 15q (13,14), as well as genetic variants in CTNND2, as being associated with myopia (15). Recently, a missense variant in LEPREL1 (encoding prolyl 3-hydroxylase 2 [P3H2]), a 2-oxoglutarate-dependent dioxygenase that hydroxylates collagen molecules, was associated with an autosomal-recessive form of high myopia and early-onset cataracts in an Israeli-Bedouin kindred (16).…”
Section: Introductionmentioning
confidence: 82%
“…Outlier MSE measurements were set as missing values. The average of the MSE in the right and left eyes was used in the analyses 43,44 , and likewise for AXL and RCC. The primary outcome measure was MSE at age 15.…”
Section: Discussionmentioning
confidence: 99%
“…GJD2 is an established susceptibility gene for increased axial length and myopic refraction 11,23 . In the current study, these associations with GJD2 were replicated in our independent Japanese sample collections.…”
Section: Resultsmentioning
confidence: 99%
“…The associations with axial length and corneal curvature were successfully replicated in both Chinese and Caucasian cohorts. In addition, the WNT7B genotype strengthened the effects of GJD2, a widely replicated myopia susceptibility gene 11,23 . Furthermore, the WNT7B polymorphism rs10453441 was also significantly associated with extreme myopia.…”
Section: Discussionmentioning
confidence: 99%